Shifts in endocrine homeostasis and preventive hormone replacement therapy: extending the Women's Health Initiative globally. Issue 1 (December 2016) - Ball, Jacob; Chen, Xinguang
Abstract Background Reducing disease risk for women after menopause is global health issue. A major portion of the Women's Health Initiative (WHI) consisted of two clinical trials involving 161, 809 post-menopausal women aged 50–79 that tested the effect of hormone replacement therapy (HRT) on reducing cardiovascular disease and other secondary outcomes. Previous analyses of the data reveal that HRT should not be recommended for post-menopausal women, but show potential benefits for younger women. Thus, there may be a critical period just prior to or during the early stages of menopause where HRT could be both safe and beneficial. Main body Menopause marks the beginning of a process of non-reversible reduction in estrogen by which estrogen levels decline progressively, followed by a reduction in estrogen receptors. This results in periods of hormone-receptor imbalances, exacerbating the effects of lower serum estrogen and is considered the primarily endocrinal source of menopause symptoms. Eventually a hormone-receptor balance is achieved at a lower level. Here, we purport that the negative outcomes from WHI trials were primarily due to the fact preventive HRT was initiated in women who had already achieved hormone-receptor equilibrium at lower hormonal levels. Conclusion We argue for further HRT clinical trials in women at varying stages of menopause, including pre-menopause and early menopause, and in women from different countries. Variation across countries and subgroups in how women experience menopause and perceive menopause symptoms suggest that biocultural differences should be considered in both study design and measurement approaches to test the effectiveness of HRT. Particularly, we recommend longitudinal studies to assess changes in hormonal level over time, and to detect the "most effective period" for HRT to reduce health risk for women going through the whole menopause period.